2002
DOI: 10.1074/jbc.m203734200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by Protein Kinase Cδ Is Independent of Its Kinase Activity

Abstract: Protein kinase C, a multigene family of phospholipiddependent and diacylglycerol-activated Ser/Thr protein kinases, is a key component in many signal transduction pathways. The kinase activity was thought to be essential for a plethora of biological processes attributed to these enzymes. Here we show that at least one protein kinase C function, the induction of apoptosis by protein kinase C␦, is independent of the kinase activity. Stimulation of green fluorescent protein-protein kinase C␦ fusion protein with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 46 publications
4
34
0
Order By: Relevance
“…Herein, it is believed that translocation of a specific PKC isoform to a cellular compartment is the major determinant of its specificity and function [28]. Indeed, similarly to results from mammalian cells [28,29], we found that in the absence of activators both nPKC- and - were detection of PKC- mitochondrial localisation [33]. Another work also showed that although induction of apoptosis via activation of PKC- and - increased cytochrome c release and accumulation of ROS, no PKC- and - were detected in mitochondria [8].…”
Section: Coleon U Also Induced Yeast Growth Inhibition But Only In Cesupporting
confidence: 77%
“…Herein, it is believed that translocation of a specific PKC isoform to a cellular compartment is the major determinant of its specificity and function [28]. Indeed, similarly to results from mammalian cells [28,29], we found that in the absence of activators both nPKC- and - were detection of PKC- mitochondrial localisation [33]. Another work also showed that although induction of apoptosis via activation of PKC- and - increased cytochrome c release and accumulation of ROS, no PKC- and - were detected in mitochondria [8].…”
Section: Coleon U Also Induced Yeast Growth Inhibition But Only In Cesupporting
confidence: 77%
“…Thus, the study by Guo and colleagues clearly demonstrates that neither the phosphorylation nor catalytic activation of PKC␦ is required for the H 2 O 2 -induced physical interaction of PKC␦ with Shc or the subsequent translocation of the complex in neonatal cardiomyocytes (9). Consistent with the study by Guo and colleagues, studies in rat aortic smooth muscle cells have provided evidence that PKC␦ exhibits kinase-independent functions (8).…”
Section: Of Pkc␦ This Complex Is Insensitive To An Inhibitor Of Src supporting
confidence: 71%
“…PKC activates the MAPK ERK1/2 pathway by stimulating the Raf-Ras-MAPK kinase pathway in different cell types (26,27). In this study, we showed that the protective effect of activation of PKC is at least in part associated with activation of ERK1/2 induced by TRAIL (23).…”
Section: Discussionmentioning
confidence: 59%